Eurycoma longifolia extract exhibits anti-atherosclerotic effects in an in-vivo model - A. J., Fakhria; Saxena, Anil Kumar; Al-Ani, Imad Matloub Dally; A.Talib, Norlelawati; Hanim, M. R.; Ku Zaifah, Norsidah (2015)
Hyperlipidaemia remains the most important risk factor for cardiovascular events mainly the atherosclerosis, a progressive process occurs within the walls of large and medium arteries. Eurycoma Longifolia (EL), Simaroubaceae is a herb that has been used since ancient times to combat many health problems and for other medicinal purposes. Its effects are generally attributed to its bioactive constituents. To examine the effects of EL on lipid profile and intima media thickness (IMT) in aorta of Sprague Dawley (SD) rats by high- fat induction. Healthy male SD rats were divided into 4 groups of 6 animals and treated for 12 weeks as follow: Group I was given only normal diet, Group II was given normal diet and EL, Group III was given only high fat diet (HFD), Group IV was given HFD and EL extracts. The thickness of intima media of aortas were photographed and measured with Dino-Captured® 2.0. Statistical significance was determined by one way (ANOVA). P values less than 0.05 were considered significant. In this study, the aortic IMT was significantly increased in the HFD group than that of ND (p< 0.05), on the other hand the aortic IMT was significantly reduced in HFDEL group than that of HFD group (p<0.05). Results represent mean (SD) of 5 rats per group. Results of this study showed that the aqueous extract of EL attenuated the formation of atherosclerotic plaques in aorta of rats by HFD induction.